Co-operative inquiry: A research policy method for secondary education in Nigeria - Olayiwola, Shina (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
This article examines the level of research involvement among educational stakeholders in the process of educational policy-making and implementation in Nigeria. It attributes the transformational challenges confronting the secondary school system in Nigeria to the epistemological question: “What is the relationship between the knower or would-be knower and what can be known?” This is premised on the idea that the research process that led to the 6-3-3-4, or the “new” 9-3-4 system of education from the 6-5-2-3 system of education, did not involve the participants as co-researchers and co-subjects in their relationship. This article argues for co-operative inquiry as an alternative participatory, action research method for ameliorating these transformational challenges in the Nigerian secondary school system.